Teaching and learning technology (Addison-Wesley, 1993)
The book pffers an understanding of what technology is how it should be taught - providing a valuable resource for anyone wishing to consider the pedagogic implications of implementing a broad technological curriculum for all pupils. Part 1 begins by setting the context for current initiatives in technology education. Part 2 addresses issues relating to the nature of technological capability, and poses questions about the practical action. Part 3 explores the background to the way children learn technology, ranging through investigations into children's work in science and maths, practical work and work with computers. Part 4 develops the theme of children's learning in several areas of direct interest. Part 5 concludes by considering a range of teaching methods and approaches including how teachers respond when faced with a requirement to begin teaching something new